Literatur Review: Faktor Penyebab Rendahnya Akseptor KB dengan Metode Kontrasepsi Jangka Panjang - Dahniar Dahniar; Arisna Kadir; Uliarta Marbun; Lili Purnama Sari (Poltekkes Kemenkes Padang, 2024)
Acceptors are family planning participants of childbearing age couples where one person uses one of the contraceptive methods to prevent pregnancy either through a program or non-program. Family planning is an action to help individuals or married couples to avoid unwanted births, get births that are desired, regulate the interval between births (Anggraini, 2021). The birth rate in Indonesia has increased, recorded in 2018 the birth rate was 264,161.6 people and in 2022 there were 275,773.8 people, this is related to the use of contraception (MKJP) which also did not reach the target. The types of contraceptives most widely used by active Non-MKJP family planning participants are: Injections 5,990 people (39.7%), Pills 4,672 people (31%), Condoms 1392 people or (9.2%) while active family planning participants MKJP namely: Implant 969 (6.4%) and, IUD 221 people (1.5%), MOP 19 people (0.1%), MOW 131 people (0.9%) (BKKBN Baubau City Profile, 2018). The purpose of this study was to determine the factors causing the low acceptance of family planning with MKJP. This study uses a type of literature review to examine the factors of age, parity, knowledge and husband support by taking data from Google Scholar with a total population of 677 journals with 10 samples. The results of the assessment concluded the magnitude of the factors of parity, age, knowledge and husband support on the acceptor's decision not to use MHJP.